Analysis of Demand Observed in the Polish Housing Market 2019-2021 - Grzegorzewski, Michał (Analiza popytu zaobserwowanego na polskim rynku mieszkaniowym w latach 2019-2021, 2022)
Consumer demand has a key impact on the development prospects of the national economy, and the construction sector accounts for a significant share in the structure of Polish GDP. The period of crisis is a special environment conditioning social behaviour and, at the same time, the first stage of the new business cycle. Understanding the social reactions prevailing in this phase influences the forecasting of further parts of the cycle. The aim of the study was to analyse the impact of the economic environment conditioned by the COVID-19 epidemic on the behaviour of residential real estate buyers. In order to achieve the goal, empirical non-reactive and survey research were carried out. The obtained results show why flats in Poland are perceived as a safe form of investment and provide a helpful tool for forecasting the future of the Polish housing market.
Ekonomia XXI Wieku = Economics of the 21st Century, 2022, Nr 25, s. 5-18
Keywords: construction industry; housing market; demand; crisis; COVID-19; budownictwo; rynek mieszkaniowy; popyt; kryzys